Major Gram-negative bacterial causes isolated from apparent Healthy and diarrheic foals in Egypt, prevalence, identification and antibiotic susceptibility profiles - Fouad, Ehab A.; Dapgh, Amany N.; Shahein, Momtaz A.; Riad, Emad M.; Syame, Sohier M.; Hakim, Ashraf S. (Journal of Advanced Veterinary Research, 2024)
Diarrhea is one of the most significant illnesses affecting young foals and may be manifested in more than half of foals up to 3 months of age. Numerous infectious causes have been involved but bacterial pathogens are concerned. This study aimed to assess and identify the prime Gram-negative bacteriological etiology of Arabian horse foals’ diarrhea in Egypt and to designate the antibiotic susceptibility profiles of the isolated microorganisms. Rectal swabs and internal organs were obtained from 216 foals (89 diarrheic and 127 apparently healthy), aged 1 week to 1 year old, reared in Arabian horse farms in Great Cairo, Egypt during a period extended from March 2022 to December 2022. Conventional bacteriological examination was performed using selective media persuaded by routine and advanced biochemical tests. The isolation displayed 648 bacterial isolates; 452 (68.6%) were Gram-negative with the mixed isolation representing about 28%. Escherichia coli constituted the most prevalent; 110 / 452 (24.34%); 65 in apparently healthy foals and 45 among diarrheic ones. The second was Klebsiella pneumoniae (72, 15.92%) at which 50, (15.67%) were found to expose the highest causative agent recovered from diarrheic foals. Imipenem, quinolones, and trimethoprim/sulfamethoxazole were the most effective versus Gram-negative species isolated from diarrheic foals while ampicillin and tetracycline were of no effect. The phenotypic antibiotic susceptibility test revealed a picture of multidrug resistance (MDR) as 111 isolates (28.71%) showed resistance to three or more antibiotics belonging to different groups. The results demonstrated that Klebsiella pneumonia was the highest MDR species (54.16%) followed by Pseudomonas aeruginosa, Salmonella enterica, and Escherichia coli isolates by 43.9, 32.1 and 30.9 % respectively. In conclusion, Gram-negative bacteria constituted the major causative agents of diarrhea in the Arabian foals. The most effective antibacterial drugs were imipenem, quinolones, and trimethoprim/ sulfamethoxazole. The issue of the existence of multidrug resistance isolates should be considered for proper therapy of foal diarrhea.